Thiazide and Thiazide-like Diuretics in the Treatment of Arterial Hypertension: are there Any Differences? - A. I. Kochetkov (Рациональная фармакотерапия в кардиологии)
In the current clinical guidelines for arterial hypertension, diuretics are considered one of the first line antihypertensive drugs, which are equivalent in their effectiveness to other main pharmacological classes used in the treatment of this disease. To date, much attention is paid to both the antihypertensive potential of diuretics and their safety profile and ability to influence prognosis. In this regard, a rational approach to the consideration of the clinical and pharmacological properties of these drugs is the isolation of thiazide and thiazide-like drugs among them, which is reflected in international clinical guidelines. Among thiazide-like diuretics, indapamide occupies a special place, favorably distinguished by its antihypertensive properties, metabolic neutrality, as well as the ability to improve the prognosis and favorably influence hard endpoints in the form of mortality rates in patients with hypertension. A unique feature of indapamide is also the presence, in addition to the direct diuretic effect, pleiotropic properties, including, in particular, some antagonism towards calcium and beneficial effects on arteries. This drug has been studied in a large number of studies, including such "difficult" categories of patients as the elderly and patients with diabetes mellitus, where indapamide has proven its powerful target-organ protective potential and metabolic neutrality, distinguishing it among both thiazide-like and thiazide diuretics. Indapamide provides a comprehensive target-organ protection at the level of the heart, blood vessels, kidneys and brain. Based on this, it can be expected that the widespread use of this drug as part of a first-line combination antihypertensive therapy will not only achieve target blood pressure levet in most patients with hypertension, but also provide an improved prognosis and improve the quality and duration of their life.